A Comprehensive Analysis of Protecting Civilians under International Humanitarian Law and Islamic Law in Afghanistan - Bhagyamma , G; Ramesh, (Trinity Law Review, 2024)
This research delves into the multifaceted impact of the protracted Afghan conflict on society, examining its consequences for the environment, children, and individuals with disabilities. It explores how International Humanitarian Law (IHL) and Islamic law intersect in addressing the challenges faced by these vulnerable populations. The article highlights the importance of IHL, the complexities of Jus ad Bellum and Jus in Bello principles, and the significance of safeguarding children, the environment, and persons with disabilities during armed conflicts. It emphasizes the role of international organizations and conflict parties in upholding these principles to protect Afghanistan’s vulnerable populations and their rights.
Keywords: Afghan conflict; International Humanitarian Law; Vulnerable populations Islamic law and Child protection